Interrelation of inflammatory endothelial markers with the severity of bronchial asthma in children - Butov, Dmytro (Medicinski časopis, 2019)
Background: Monocyte chemoattractant protein-1 (MCP)-1 and vascular intercellular adhesion molecule of endothelin-1 (sVCAM-1) are key regulators of the inflammation sites infiltrated with monocytes. Methods: The levels of MCP-1 and sVCAM-1 during BA exacerbation on the background of therapy in children with various degrees of BA severity as well as correlation relationships between MCP-1, sVCAM-1 and parameters of external respiration function were determined. Results: The level of MCP-1 and sVCAM-1 in all groups of the examined patients at the period of exacerbation of the disease was significantly higher than in children of the control group. On the background of therapy the levels of MCP-1 and sVCAM-1were decreased in patients of all groups, regardless of BA severity. Negative correlation relationships between MCP-1 and FEV1, PEF, VC, FVC, FEV1/FVC were revealed before and after the therapy. Conclusions: The increased levels of the above mentioned biomarkers were preserved on the seventh day of therapy. This testifies to the involvement of these chemokines into the formation and prolongation of the inflammatory process. The revealed negative correlation between MCP-1 and the main parameters of pulmonary function testified to participation of chemoattractant MCP-1 in chronic inflammation of the airways.